Hibah Alat Pencacah Rumput oleh Mahasiswa KKM 67: Meningkatkan Kemandirian Desa Mekar Agung dalam Produksi Pupuk Organik Cair - Solehudin Solehudin; Try Adhi Bangsawan; Milawati Valantia; M. Elang Adriansyah; Rico Sandi; Novia Safitri (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Mekar Agung Village has abundant agricultural potential, but the utilization of green waste for liquid organic fertilizer is still not optimal. Seeing this problem, KKM 67 students initiated a grant of grass chopper tools to support the production of liquid organic fertilizer in the village. This community service activity aims to increase village independence in processing green waste into fertilizer that can increase soil fertility and agricultural productivity. The method of implementing the activity includes the stage of socialization to the community regarding the importance of organic fertilizer, training in the use of grass chopper tools, and assistance in the production of liquid organic fertilizer. Through a participatory approach, the community is actively involved in every stage of the activity. The results of this activity show an increase in the community's ability to process grass waste into liquid organic fertilizer, as well as increasing awareness of the importance of environmentally friendly agriculture. The grass chopper tools that were donated have also proven effective in accelerating the process of processing green waste. This activity is expected to continue independently and contribute to economic and environmental development in Mekar Agung Village.